2023
DOI: 10.3390/nu15020406
|View full text |Cite
|
Sign up to set email alerts
|

SLC6A4 DNA Methylation Levels and Serum Kynurenine/Tryptophan Ratio in Eating Disorders: A Possible Link with Psychopathological Traits?

Abstract: Background: The incidence of eating disorders (EDs), serious mental and physical conditions characterized by a disturbance in eating or eating-related behaviors, has increased steadily. The present study aims to develop insights into the pathophysiology of EDs, spanning over biochemical, epigenetic, psychopathological, and clinical data. In particular, we focused our attention on the relationship between (i) DNA methylation profiles at promoter-associated CpG sites of the SCL6A4 gene, (ii) serum kynurenine/try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…However, altered methylation profiles in AN compared to healthy controls were identified for only ten genes. These genes are related to mood regulation and neurotransmitter release (serotonin, dopamine, alpha-synuclein) [57,58,[66][67][68], social attachment (oxytocin) [62,69], appetite regulation (leptin, ghrelin) [53,68,70], lipid metabolism and energy homeostasis (NR1H3) [45,49,54,61], extracellular matrix organization (TNXB) [45,49,54,61] and regulation of gene expression (HDAC4) [49,71]. Intriguingly, all genes except for leptin and, more recently, serotonin showed an increased methylation level in patients with AN compared to healthy controls [53,66].…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, altered methylation profiles in AN compared to healthy controls were identified for only ten genes. These genes are related to mood regulation and neurotransmitter release (serotonin, dopamine, alpha-synuclein) [57,58,[66][67][68], social attachment (oxytocin) [62,69], appetite regulation (leptin, ghrelin) [53,68,70], lipid metabolism and energy homeostasis (NR1H3) [45,49,54,61], extracellular matrix organization (TNXB) [45,49,54,61] and regulation of gene expression (HDAC4) [49,71]. Intriguingly, all genes except for leptin and, more recently, serotonin showed an increased methylation level in patients with AN compared to healthy controls [53,66].…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…Altered methylation patterns in patients with AN were identified for the following ten genes: SLC6A4, SLC6A3/DAT, OXTR, DRD2, LEP/LEPR, NR1H3, GHSR1a, TNXB, HDAC4, and SNCA. Interestingly, except for the leptin gene (LEP), which was identified in the only longitudinal candidate study [53], and recently the serotonin receptor gene (SLC6A4) [66], all other genes showed hypermethylation in patients with AN compared to healthy controls (Table 2). The serotonergic system has been proposed to have a distinct impact on the pathophysiology of AN, given its pivotal role in regulating appetite, satiety, and mood [38,99].…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a crucial role in the reuptake of serotonin from the synaptic cleft into presynaptic neurons, terminating neurotransmission and regulating serotonin signaling. Dysfunction or dysregulation of SLC6A4 can lead to alterations in serotonin levels and signaling, which have been implicated in various neuropsychiatric disorders, including depression, anxiety disorders, schizophrenia, and obsessive-compulsive disorder (OCD) [ 10 , 33 , 35 , 36 ]. Antiporters transport two different molecules in opposite directions (one substrate moves into the cell, another moves out) across the membrane (e.g., SLC4A1/AE1).…”
Section: Slc Gene Family and Its Role In Ion Transportmentioning
confidence: 99%
“…Anorectic and bulimic patients did not manifest changes in L-kynurenine levels compared to controls. There was a small but significant increase in the TRP level among purging AN, as well as a small decrease in the L-kynurenine/TRP ratio [ 54 ]. Excessive physical activity in both groups of patients with AN resulted in a lower L-kynurenine level and higher TRP compared to non-exercising patients [ 54 ].…”
Section: Tryptophan and Kynurenines In Anorexia Nervosamentioning
confidence: 99%